Non-canonical splice junction processing increases the diversity of RBFOX2 splicing isoforms. (March 2022) - Choi, Sunkyung; Cho, Namjoon; Kim, Kee K.
Abstract: The underlying mechanisms of splicing regulation through non-canonical splice junction processing remain largely unknown. Here, we identified two RBFOX2 splicing isoforms by alternative 3' splice site selection of exon 9; the non-canonical splice junction processed RBFOX2 transcript (RBFOX2-N.C.) was expressed by the selection of the 3' splice GG acceptor sequence. The cytoplasmic localization of RBFOX2-C., a canonical splice junction-processed RBFOX2 transcript, was different from that of RBFOX2-N.C., which showed nuclear localization. In addition, we confirmed that RBFOX2-C. showed a significantly stronger localization into stress granules than RBFOX2-N.C. upon sodium arsenite treatment. Next, we investigated the importance of non-canonical 3' splice GG sequence selection of specific cis -regulatory elements using minigene constructs of the RBFOX2 gene. We found that the non-canonical 3' splice GG sequence and suboptimal branch point site adjacent region were critical for RBFOX2-N.C. expression through a non-canonical 3' splice selection. Our results suggest a regulatory mechanism for the non-canonical 3' splice selection in the RBFOX2 gene, providing a basis for studies related to the regulation of alternative pre-mRNA splicing through non-canonical splice junction processing. Graphical Abstract: ga1 Highlights: RBFOX2 exon 9 has an alternative 3' splice site (GG or AG). Two types of RBFOX2 splicing isoforms differ in subcellular localization. The 3' splice GG sequence and suboptimal branch point site are important for GG 3' splice site selection.